The impact of Helicobacter pylori and intestinal helminth infections on gastric adenocarcinoma and inflammatory bowel disease in Sub-Saharan Africa - Setshedi, Mashiko; Watermeyer, Gillian (Frontiers in Medicine, 2022)
Gastric adenocarcinoma (GCA) is the 5th leading cancer globally with an estimated 1.1 million cases reported in 2020. Ninety percent of non-cardia GCAs are attributable to Helicobacter pylori (H. pylori), the most prevalent bacterial infection globally. Rates of H. pylori infection are highest in Sub-Saharan Africa (SSA), yet surprisingly low numbers of GCAs are reported in the region. A similar phenomenon is seen with the Inflammatory Bowel Diseases (IBD), Crohn’s Disease and Ulcerative Colitis. These disorders have risen dramatically over the past century in high income countries across the globe, with sharp increases noted more recently in newly industrialized regions. In contrast IBD is rare in most regions in SSA. For both diseases this may reflect under-reporting or limited access to diagnostic modalities, but an alternative explanation is the high burden of infection with gastrointestinal parasites endemic to SSA which may attenuate the risk of developing GCA and IBD. In this mini review we discuss the complex interplay between these microorganisms, GCA, and IBD, as well as a possible protective role of H. pylori and the development of IBD.